Scientific and technological assessment of iron pyrite for use in solar devices - Shukla, Sudhanshu (2019)
Iron pyrite (FeS2) holds an enormous potential as a low cost and non‐toxic photoelectrochemical and energy‐harvesting material owing to its interesting optical, electronic, and chemical properties along with elemental abundance. In this Review, low cost and scalable processing techniques to synthesize phase‐pure pyrite thin films and nanocubes are described, and the application of this material in various energy‐harvesting devices such as dye‐sensitized solar cells, photodiodes, and heterojunction solar cells is discussed. A detailed analysis of the electron transport in single‐crystal iron pyrite is presented to shed light on its bulk‐ and surface‐conduction properties, which could be useful in designing better pyrite solar cells and could be exploited for novel device architectures. Finally, future prospects and directions are discussed.